PENGARUH PERPUTARAN MODAL KERJA, AKTIVA TETAP, DEBT TO TOTAL ASSETS RATIO DAN EARNING PER SHARE TERHADAP RETURN ON ASSETS PADA PERUSAHAAN TRADE, SERVICE AND INVESTMENT DENGAN CURRENT RATIO SEBAGAI PEMODERASI - Annisa Nauli Sinaga; Putri Handayani Singh; Veronica Veronica; Shelly Wijaya (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Trade, Service and Investment company is one of the fastest growing corporate sectors in Indonesia. This is due to the many needs and desires of the community are unlimited. Where the company established of course also has the main goal of obtaining maximum profit/profit from the activities carried out in developing the company. The purpose of this study is to determine the effect of Working Capital Turnover, Fixed Asset Turnover, Debt To Total Assets Ratio and Earning Per Share on Return On Assets with Current Ratio as Moderating. The sampling method used is purposive sampling. Sampel used by 29 Trade, Service and Investment companies using secondary data from the Indonesia Stock Exchange for the period 2018-2020. The data analysis models used in this study are multiple linear regression analysis, determination coefficient, simultaneous significance test, individual parameter significance test, and moderation regression analysis model. The final result of this study is Working Capital Turnover, Fixed Asset Turnover,Debt to Total Asset Ratio and Earning per Share simultaneously positively and significantly affect profitability in Trade, Service &Invesment companies listed on the Indonesia Stock Exchange. Partial Turnover of Working Capital, Settlement of Fixed Assets, and Debt To Total Assets Ratio has no effect and is insignificant to profitability, while Earning Per Share has an effect and is positive and significant to profitability. While the Current Ratio is not a moderation variable, so the Current Ratio cannot strengthen or weaken the relationship between independent and dependent variables. Keywords: Working Capital Turnover, Fixed Asset Turnover, Debt To Total Assets Ratio, Earning Per Share, Return On Assets, Current Ratio.